2016
DOI: 10.1007/s13105-016-0502-8
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone changes after consumption of a sodium-bicarbonated mineral water in humans. A four-way randomized controlled trial

Abstract: Abnormally high aldosterone levels are associated to hypertension and cardiovascular disease. A sodium-rich mineral water was previously shown to reduce several markers of cardiovascular risk and did not increase blood pressure in healthy adults. We aimed to study the effects of consuming the same mineral water compared to a control water on aldosterone levels, and if the effects vary due to the presence of meal in healthy adults. The design was a four-way randomized controlled crossover 120-min-postprandial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…However, there may be several interacting factors. In this regard, estrogens are related to higher levels of cholesterol transported by high-density lipoproteins (HDL-cholesterol) and aldosterone that may partly explain lower atherosclerosis and hypertension risk [39]. However, age has been suggested to exert higher influence than hormones as estrogens explain about 25% of the phenotype differences related to cardiovascular risk, and thus menopausal women have higher cardiovascular risk than fertile women mainly due to age [40].…”
Section: Iron Excess and Cardiovascular Risk 31 The Iron Hypothesismentioning
confidence: 99%
“…However, there may be several interacting factors. In this regard, estrogens are related to higher levels of cholesterol transported by high-density lipoproteins (HDL-cholesterol) and aldosterone that may partly explain lower atherosclerosis and hypertension risk [39]. However, age has been suggested to exert higher influence than hormones as estrogens explain about 25% of the phenotype differences related to cardiovascular risk, and thus menopausal women have higher cardiovascular risk than fertile women mainly due to age [40].…”
Section: Iron Excess and Cardiovascular Risk 31 The Iron Hypothesismentioning
confidence: 99%
“…These 4 chronic studies revealed no consistent modulation and relation between circulating aldosterone and urinary sodium excretion [56,57,62,63]. However, significant acute effects upon circulating aldosterone were described with 3 similar NaHCO 3 − -rich (also chloride-rich) mineral-rich waters [2 being the same used by Schoppen et al [61] and Pérez-Granados et al [58] and 1 similar to the ones from Toxqui et al [63], Schoppen et al [61] and Pérez-Granados et al [58] studies] and an association with urinary sodium excretion was proposed [107,108]. In the two cross-over trials, in healthy postmenopausal women [107] and healthy younger women [108], the authors found a significant decrease in circulating aldosterone 120 min after mineral-rich water ingestion, with and without a meal [107,108]; water intake significantly increased urinary sodium excretion in 7-h urine [107].…”
Section: Discussionmentioning
confidence: 99%
“…However, significant acute effects upon circulating aldosterone were described with 3 similar NaHCO 3 − -rich (also chloride-rich) mineral-rich waters [2 being the same used by Schoppen et al [61] and Pérez-Granados et al [58] and 1 similar to the ones from Toxqui et al [63], Schoppen et al [61] and Pérez-Granados et al [58] studies] and an association with urinary sodium excretion was proposed [107,108]. In the two cross-over trials, in healthy postmenopausal women [107] and healthy younger women [108], the authors found a significant decrease in circulating aldosterone 120 min after mineral-rich water ingestion, with and without a meal [107,108]; water intake significantly increased urinary sodium excretion in 7-h urine [107]. The two mineral-rich waters, also fluorurate, tested in this last study, by Schoppen et al, behaved similarly but with the lower sodium content mineral-rich water showing a non-significant impact versus low-mineral content control water; no changes in urinary potassium, chloride and bone mineral excretion and urinary pH were observed [107].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the physiological response of aldosterone as fasting levels tended to be lower with BW at week 8 compared to baseline ( Table 2 ). In two postprandial randomised, controlled trials, BW decreased aldosterone levels after 120 min of consumption [ 31 , 32 ] and increased sodium excretion in 7-h urine [ 31 ]. As changes in fasting urinary sodium by BW did not reach significant levels in the present study, we suggest that the inhibition of the renin-angiotensin-aldosterone system could be a short-term homeostatic mechanism which helps to maintain blood pressure in the long term.…”
Section: Discussionmentioning
confidence: 99%